Middle-Income Trap or Development Trap and its Budgetary Effects - Csath, Magdolna (Public Finance Quarterly, 2023)
Recently there have been debates about whether the Hungarian economy could end up in a so-called middle-income trap in the near future. Some argue this risk is on the rise. Others focus more on whether this threat is even real and how it could be avoided if indeed it is. What do we mean by middle-income trap? This isn’t clarified in either Hungarian or international literature. There are doubts about whether it is even possible to measure the success of an economy and of society with the income growth indicators researchers usually use to demonstrate the trap situation, or if we should instead take a closer look at the evolution of sustainable growth indicators. The topic is made particularly important by the fact that for budgetary balance, it is important that income sources are created in a consistent and reliable way, which, besides the yearly growth rate, also depends on balanced development. This article analyzes what the literature means by middle-income trap and argues that there is no way to reliably prove a potential halt of development based on the indicators used to measure it. Therefore, it introduces new indicators also measuring growth and examines the situation of multiple countries and their development paths based on international data, using these indicators. Finally, it concludes that the Hungarian economy’s growth rate could primarily be accelerated by modernizing the knowledge structure of the economy and by increasing the share of activities with a high added value and those that incorporate knowledge and innovation.